Novel Management of Peri-Aortitis after Endovascular Repair of Abdominal Aortic Aneurysm. (2019) - Trinder, Matthew; Mwipatayi, Bibombe P.; Siew, Teck; Lim, Andrew; Altaf, Nishath
Abstract : Introduction: The management of peri-aortitis, a rare complication after endovascular aneurysm repair (EVAR) of abdominal aortic aneurysms (AAA), is described in a patient with a solitary kidney. Report: A 64 year old man who developed peri-aortitis after elective EVAR for a 6.6 cm infrarenal AAA is reported. Peri-aortitis was diagnosed two months after the procedure and was successfully treated with corticosteroids. Conclusion: There is no clear consensus on the best medical therapy for peri-aortitis secondary to EVAR. Peri-aortitis must be considered in patients with ongoing systemic symptoms of inflammation after EVAR, and early management is crucial to the early resolution of symptoms. Highlights: Peri-aortitis is a rare complication after endovascular aortic aneurysm repair. Peri-aortitis commonly presents with abdominal pain or ureteric obstruction. Peri-aortitis can be diagnosed with positron emission tomography-computed tomography and labelled white cell scan. Peri-aortitis can be treated appropriately with oral steroids.